2014
DOI: 10.1016/j.jped.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux disease: exaggerations, evidence and clinical practice

Abstract: there have been few randomized controlled trials that assessed the management of GERD in children and no examination can be considered the gold standard for GERD diagnosis. For these reasons, there are exaggerations in the diagnosis and treatment of this disease, which need to be corrected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 70 publications
0
35
0
12
Order By: Relevance
“…All the children examined had received a positive diagnose for GERD by the 24-hour pH monitoring test, and they were referred for further treatment and follow-up. The treatment objectives were to relief the symptoms, promote adequate growth and weight gain and prevent complications associated with GERD [14]. A study suggested that the progression of tooth surface loss would have been even more extensive in GERD patients with uncontrolled acid reflux [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the children examined had received a positive diagnose for GERD by the 24-hour pH monitoring test, and they were referred for further treatment and follow-up. The treatment objectives were to relief the symptoms, promote adequate growth and weight gain and prevent complications associated with GERD [14]. A study suggested that the progression of tooth surface loss would have been even more extensive in GERD patients with uncontrolled acid reflux [15].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 72.1% of the children were not taking GERD medication at the time of the oral examinations and this was not statistically significantly associated to dental erosion. Prescription medication should be considered as part of the treatment for GERD which includes changes in behavioral and dietary habits [14].…”
Section: Discussionmentioning
confidence: 99%
“…(5,14) The small gap between meals, the positioning and handling of the child in the postprandial period may contribute to the presence of gastroesophageal reflux (GER), and in children who are more sensitive to the presence of gastric contents into the esophagus, it can trigger symptoms similar to esophagitis, justifying the suspicion diagnosis of gastroesophageal reflux. (5,9,16) According to testimonies, vomiting and/or regurgitation are present in the lives of these children, causing anxiety in parents. This fact requires further approximation of nurses, in an attempt to minimize this situation with care and the guidance appropriated to the level of understanding of the family.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the nurse has an important role with food guidance, such as not offering acid, fatty or forbidden foods like chocolate and soda, as well as maintaining a fractioned and preferably pasty diet. (3,16,20) Other features presented by children with gastroesophageal reflux are irritability, excessive crying, sleep disorders, hiccups, restlessness and refusal to eat. These symptoms are routine reasons for consultations, especially for infants younger than three months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation